Pengaruh Variasi Diameter Dan Jarak Kolom Campuran Abu Terbang Dan Abu Dasar Dengan Pola Segi Empat Terhadap Daya Dukung Tanah Gambut - Aisyah Putri; Muhardi Muhardi; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Group of columns that inserted in the soft soil will increase shear strength and density of the soil, reduce soil settlement and liquefaction potential, and increase bearing capacity ofthe soil. Things that must be considered in columns design are diameter, length, space, and pattern of the columns group. This study aims to see the effect of diameter and columnspacing on bearing capacity of peat. Variation of diameter that used in this study are 3 cm, 4 cm, and 5,5 cm. Variation of space that used in this study are 1,25D, 1,5D, and 1,75D.The results of laboratory testing indicate that increasing the diameter dan decreasing the space between columns will increase bearing capacity of stabilized peat. Maximumbearing capacity given by 5,5 cm diameter and 1,25D space variation. The increasing of bearing capacity reaches 74,49%. The results of theoretical analysis give different tendency.Increasing of diameter dan space between columns will increase bearing capacity of the stabilized peat. This tendency difference is due to the influence of overlap between soils withinthe unit cell due to the very close space of the column.Keywords : stone column, diameter, space, bearing capacity